Gut microbiota-derived imidazole propionate: an emerging target for the prevention and treatment of cardiometabolic diseases - Zeng, Yan; Wu, Qi; Guo, Man; Teng, Fangyuan; Jiang, Chunxia; Chen, Jiao; Tan, Xiaozhen; Zeng, Chen; Long, Yang; Law, Betty Yuen-Kwan; Xu, Yong (Frontiers in Endocrinology, 2025)
Despite significant advancements in prevention and treatment, cardiometabolic diseases continue to pose a high burden of incidence and mortality. The chronic progression of these diseases necessitates the identification of early and complementary therapeutic targets to elucidate and mitigate residual risks in patient care. The gut microbiota acts as a sentinel between internal and external environments, transmitting modified risks associated with these factors to the host. Imidazole propionate (ImP), a histidine metabolite originating from the gut microbiota, gained attention after being found to impair glucose tolerance and insulin signaling several years ago. Epidemiological studies over the past five years have demonstrated a robust correlation between ImP and an increased risk of onset of type 2 diabetes (T2D) and obesity, exacerbation of kidney traits in chronic kidney disease (CKD), progression of atherosclerotic plaques, and elevated mortality rates in heart failure (HF). These findings suggest that ImP may serve as a pivotal target for the prevention and treatment of cardiometabolic diseases. Mechanistic insights have uncovered associations between ImP and insulin resistance, impaired glucose metabolism, chronic inflammation, and intestinal barrier damage. This review provides a comprehensive summary of the current evidence regarding the association between ImP and cardiometabolic impairment, highlighting its potential in advancing personalized approaches to disease prevention and management, and exploring the intricate interplay of diet, gut microbiota, and ImP in cardiovascular metabolic impairment. Overall, this review offers valuable insights into the multifaceted roles of ImP in cardiometabolic diseases, identifies current knowledge gaps, and discusses future research directions.